Virulence of Colletotrichum gloeosporioides causing strawberry anthracnose disease in Tucumán, Argentina = Virulencia de Colletotrichum gloeosporioides causante de la enfermedad de la antracnosis en frutilla en Tucumán, Argentina - Salazar, Sergio Miguel; Moschen, Sebastian; Mónaco, María Elvira; Castagnaro, Ana P.; Diaz Ricci, Juan Carlos (Facultad de Agronomía y Zootecnia, Universidad Nacional de Tucumán, 2019)
A fungal strain with phytopathological behaviour was isolated from strawberry leaves and fruits with symptoms of anthracnose disease in Tucumán province (north-west Argentina), and it was identified as strain L9 of Colletotrichum gloeosporioides. Inoculation experiments on different strawberry cultivars using the isolated strain revealed dissimilar phytopathological responses. Whereas the cultivars ‘Pájaro’ (accession Mendoza), ‘Milsei’, ‘Selva’ and ‘Seascape’ triggered a typical response compatible with strain L9, the cv. ‘Pájaro’ (accession Cafayate) and ‘Gaviota’ showed a typically incompatible response.